Medical physics : models and technologies in cancer research - Bajek, Anna; Bajek, Anna; Tylkowski, Bartosz; Tylkowski, Bartosz (De Gruyter STEM, 2021)
Modern cancer research is a high-tech undertaking, overlapping with many fields in the physical sciences. These include nanotechnology, engineering, immunology, and bioinformatics. This book focuses on the science and technology underlying the diagnosis and treatement of cancer. The authors offer insights into technologies including radiotherapy, modelling, and drug encapsulation.